The Effect of Zinc Supplementation on Improving Cognitive and Nutrition Status among Preschool Children Coming to Family Medicine Center Clinic in Nikla Village at Giza (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objectives: Prevalence of zinc deficiency among preschool children in the study.Impact of zinc supplementation on cognitive function and the nutritional status among preschoolchildren.Health education for healthy food and their requirement from the food regard the age and sex.Study design:This is a pre-post intervention study included 50 preschool child.Method: The children randomly assigned to receive zinc supplementation daily for 6 months according to thelevel of plasma zinc. They were A self- administered questionnaire was used included (socio-demographicdata, food frequency questionnaire and 24 hr. recall), anthropometric and cognition were assessed at thebeginning and the end of the supplementation period. In addition to health education about healthy foodthroughout the follow up 6 months.Results:-The study included males (46%) and females (54%);-There was a significant difference in weight for age and height for age between the group before and afterzinc supplementation.- A significant difference in cognitive function, which the full-scale IQ, verbal IQ and nonverbal IQ betweenthe group before and after zinc supplementation-The health education effect positively on increasing the consumption of healthy food as protein, CHO,fruits, and vegetables to the normal proportions also effect on decrease consumption of unhealthy food asmanufactured potatoes, fizzy drinks, and sweats.Conclusions: zinc supplementation has an effect on cognitive and nutrition status on preschool age.-Health education about healthy food have goodfeedback on the study.